O método SLP associado ao algoritmo CNA para o planejamento de leiaute: estudo de caso aplicado a uma movelaria na cidade de Dom Eliseu - PA - BRITO, Fredson Teixeira (2022)
The application of tools in the study of the production process in industrial environments high level of competition is something that becomes increasingly relevant given that Improvements in manufacturing flexibility are increasingly demanded. The use of analysis tools and adjustments layouts is one of the ways to search results positive for competitive organizations. This work is a theoretical description of the types existing layouts, their applicability, advantages and disadvantages in order to evaluate and propose adjustments in the current layout of the company being studied. The paper also emphasizes the application of planning layout tools. For this we performed a case study where aimed at restructuring the layout of a furniture manufacturer company. Algorithm CNA (Close Neighbour Algorithm) was employed to analyze an existing functional layout to convert it into a cell array, while the Systematic Layout Planning (SLP) was decisive as a support tool in the rearrangement of the areas of activity and departments. The results note the importance of approach pragmatic in solving questions aimed at maximizing the efficiency and quality of production process and consequently the success of organizations.